A comparative study of the biodegradability of oleic acid by sludge from a reactor fed with olive mill wastewater and sludge from a reactor fed with oleic acid - Azabou, Samia (2004)
In the present study, we investigate the biodegradability of oleic acid by sludge from anaerobic filter reactor fed with olive mill wastewater (sludge T). A comparative study was conducted using a second sludge from an expanded granular bed reactor exposed to oleic acid (sludge P). The performance of treating oleic acid and the influence of the composition of the culture media were investigated and compared. Methane production by sludge T started after a lag phase of 150 hours. However no lag phase was observed with sludge P. In contrast a higher methane production was obtained with the sludge T. The addition of nutrients (minerals and yeast extract) to culture medium reduced the lag phase of methane production by 40 hours.